Epidemiological and Molecular Study of Influenza and Parainfluenza Viruses of Respiratory System Infections in Thi-Qar Province, Iraq (Journal of Pharmaceutical Negative Results, 2022)
The current study is targeted for detection of the some important respiratory pathogen viruses which responsible for respiratory tract infections, Influenza A virus ( IAV ) and human Parainfluenza viruses (HPIVs) are considered of the causes of respiratory diseases . The current study included the examination of 150 nasal swab samples from the age of one year to the age of 70 years. The collected specimens were kept in viral transport media (VTM). RNA were extracted .The results revealed from this study are summarized in the follows : out of 150 patients suffering from respiratory tract infection only 20(13.3%) were encountered with the H1N1 virus ,23(15.3%) were HPIV1 virus , 11(7.30%) were HPIV2 ,21(14.0%) were HPIV3 .Co-infection of number of viruses appeared in 33(22.0%) patient. The sample are categorized into sex groups were H1N1viruses male 12(8.00%) higher than female 8(5.30%). HPIV1 male 13(8.70%) higher than female 10(6.70%),HPIV2 female 6(4.00%) higher male 5(3.30%), HPIV3 male 11(7.30%) higher female 10(6.70%).The distribution of H1N1virus based on age groups ,and it represents the highest percentage were 4(2.70%) less than 7 years, 3(2.00%) (57-63)years and 4(2.70%)(64-70)years .The distribution of HPIV1,2,3 based on age group , and represents the highest percentage were HPIV1 , 5(3.30%) less than 7 years,4(2.70%)(57-63)years and 5(3.30%)(64-70) years ,HPIV2, 3(2.00%)( less than 7 years) ,HPIV3 ,4(2.70%)(57-63)years ,4(2.70%)(64-70)years. H1N1virus infections in the December, January, February and March months were higher than the April , HPIV1 infections in the December, January and February months was higher than the April and March ,HPIV2 infections in the December, and January months were higher than the February, March and April ,HPIV3 infection in the March and April months were higher than the December, January and February months.